Study of Thermal Distortion in Thick Plate Using Finite Element Technique - A. Hussain, Imad; K. Radi, Samera; Y. Majeed, Mahmood (Journal of Engineering and Sustainable Development, 2008)
The aim of the present study is to represent a numerical modeling of thermal distortion and stress distribution of welded plate by using submerged arc welding .The study is carried out using existing software, which is the ANSYS package. The distortion of welded plate is found to be a nonlinear problem in geometry and material; therefore, the finite element solution is based upon the thermo-elasto-plastic and large deflection theory. The present work is an extension to a previous experimental work, where heat absorption paste (bentonite) was used to reduce distortion in welded plate, as a result of high local heating during welding process. The numerical results of distortion give reasonable indication with the distortion observed by Al-Dhamin [1]. Different rates of heat absorption are considered in this study over different area of cooling. The results show that, the distortion may be reduced significantly, by using cooling technique more efficient than the bentonite, as, using the cooling liquid of nitrogen. In this work, the optimum ratio of the cooling zone width (a) to the welded plate width (b), so as to minimize the distortion, is found equal to (a/b=0.2) for the plate at cooling temperature, equal to (30Cº, 0Cº) and (a/b=0.4) for plate with cooling temperature equal to (-30Cº). One of the experimental applications of this study is the formulation by heat source, as it is done with the structure of ships.